Geophysical Parameters For Sedimentary Rock In Northwestern Peninsula Malaysia - Hisham, Hazrul Hisham Badrul (2017)
Geophysical methods have been utilized in studying the subsurface geology of the earth. Broad range of seismic velocity and resistivity values of rocks makes it difficult to interpret the type of subsurface material. In northwestern Peninsula Malaysia, five localities have been selected to conduct seismic refraction tomography and electrical resistivity tomography to be integrated with the porosity and permeability of rocks. The rock samples from the site were tested in laboratory to obtain its porosity and permeability. In Kedah, the Semanggol Formation at Bukit Kukus, Kuala Ketil consist of Permian facies; chert and claystone.